Analysis of Health Indicators Achieved by The Periodic Plan - Pathak, Yubaraj (An ENDEAVOUR: Journal of Academia and Research, 2026)
The present research, entitled ‘Analysis of Health Indicators Achieved by the Periodic Plans of Nepal’, tries to examine the outcomes related to the health remaining within the framework of the nation's periodic planning. The very objective of this research work is to analyze and evaluate the health related indicators drawn from the evaluation of these plans through a descriptive and analytical study based on the secondary data. The researcher examines the gaps between projected targets and actual achievements of 13th, 14th, and 15th five-year plans. The findings after the research work reveal a mixed result in which the environmental and basic child health indicators are raising consistently, whereas the programs were not successful to meet their objectives exceeding targets for critical clinical indicators eve if sanitation and child mortality rates were met or exceeded. The 14th plan was successful to meet the significant gains in terms of Human Development Index and sanitation. Similarly, the fifteenth plan achieved a significant progress in health insurance sector and reduced the child stunting. Because of great earthquake of 2015 and the pandemic disease COVID-19, the Maternal Mortality Ratio and Neonatal Mortality Rate consistently failed to meet the previously set targets. Similarly, consensus about federalism emerged as one of the challenges for to achieve the objectives. The research work sums up with two facet results; the satisfactory status of infrastructure and basic access and high-level clinical outcomes which are highly vulnerable.